Pengakuan Dosa Dalam Pandangan Agama Kristen Protestan dan Kristen Katolik - Erna Apriani Zai (Medan Resource Center, 2021)
Cristianity teaches that Adam and Eve have sinned. Therefore their children and grandchildren are sinners because they are the offspring of sinner. Every child in the womb and the mother is born in a state of sin. Sin is called intherited sin and inherited sin or original sin namely sin inherited from Adam. The issue of hereditary sins is a core problem in Christian belief, without the existence of hereditary sins, of course there will be no stories about the lord jesus who redeemed human sins. There will be no need for a divine incarnation in the form of a human being to save humans, the belief in the trinity cross and so on, the main source is hereditary sin. The method used in this research is quantitative method, by using a comparative study approach is to compare to find the similarities of the two or more concepts. As for the results achieved, the same secession of confession of sins of protestant Christians has the same baptismal procedures, while the difference of confession of sins between prostestant Christians and catholic Christians in protestant religions is that only two sacraments are recognized. The goal is to know what are the differences and similarities in the remission of sins in the view of catholic and protestant Christians.